The role of the interphase on the shear induced failure of multiwall carbon nanotubes reinforced epoxy nanocomposites - Chiacchiarelli, Leonel Matias (2014)
Multiwall Carbon Nanotubes (MWCNT) with an elevated aspect ratio were chemically functionalized with amines and two types of epoxide groups. Thermogravimetric analysis and Fourier Transform-Infrared Spectroscopy (FTIR) analysis corroborated that the functionalization degree was substantial (up to 30 wt %) and the presence of a covalent bond with the MWCNT. The functionalized MWCNT (f-CNT) were incorporated into an epoxy matrix after its dispersion in the diglycidyl ether of bisphenol A (DGEBA) precursor. To induce a shear failure mode, a short-beam (SB) experimental setup was implemented. The SB shear strength (SBSS) proved that the functionalization had a strong influence on its value. For the case of pristine CNT, a neutral effect was obtained. A strong detrimental effect (−17.2% ± 9.5) was measured for the amine type f-CNT and a positive effect (up to 10.9% ± 8.9) was measured of the epoxide type f-CNT. Fractographic analysis of each formulation was correlated with SBSS performance, proving that the surface texture of the fractured samples was strongly correlated to its value. Furthermore, dynamic mechanical analysis proved that the damping factor and the crosslink molecular weight were correlated with the SBSS performance. A lower full width at half maximum of the damping factor was associated to an improvement of SBSS.